2002
DOI: 10.1042/cs1030475
|View full text |Cite
|
Sign up to set email alerts
|

Membrane structural changes support the involvement of mitochondria in the bile salt-induced apoptosis of rat hepatocytes

Abstract: A B S T R A C TThe accumulation of toxic bile salts within the hepatocyte plays a key role in organ injury during liver disease. Deoxycholate (DC) and glycochenodeoxycholate (GCDC) induce apoptosis in vitro and in vivo, perhaps through direct perturbation of mitochondrial membrane structure and function. In contrast, ursodeoxycholate (UDC) and its taurine-conjugated form (TUDC) appear to be protective. We show here that hydrophobic bile salts induced apoptosis in cultured rat hepatocytes, without modulating th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“…Under the influence of many kinds of stress factors such as ROS, Ca 2+ overloading, and toxin, mitochondrial ultrastructure and its function were easily damaged, then the active substance originally in mitochondria related to apoptosis including cytochrome C, was released into cytoplasm [14][15][16][17][18] . Recent progress in studies on apoptosis has revealed that cytochrome C is a pro-apoptotic factor.…”
Section: Discussionmentioning
confidence: 99%
“…Under the influence of many kinds of stress factors such as ROS, Ca 2+ overloading, and toxin, mitochondrial ultrastructure and its function were easily damaged, then the active substance originally in mitochondria related to apoptosis including cytochrome C, was released into cytoplasm [14][15][16][17][18] . Recent progress in studies on apoptosis has revealed that cytochrome C is a pro-apoptotic factor.…”
Section: Discussionmentioning
confidence: 99%
“…4B, E ), while DCA-NBD Supplemental Material can be found at: ( 20 ). Previous studies have also identifi ed changes in average membrane fl uidity of isolated mitochondria after exposure to toxic bile acids ( 44 ). Here, we aimed to follow in real time the changes in MOM properties and correlate these changes with the onset of MPT.…”
Section: Subcellular Distribution Of Bile Acid Derivativesmentioning
confidence: 99%
“…recruitment of Fasassociated death domain (FADD) and caspase 8 occurs [15,16,18]. TUDC was shown to protect against bile salt-induced apoptosis and a modulation of the mitochondrial membrane permeability by TUDC [20] and activation of survival pathways, such as p38 MAPK , Erks and phosphatidylinositide 3-kinase (PI3-K) were suggested to contribute to this cytoprotective effects [21,22]. However, TUDC prevents CD95 trafficking to the plasma membrane by toxic bile acids indicating that it interferes with CD95 dependent signaling towards apoptosis at a step prior to caspase 8 activation [12].…”
Section: Introductionmentioning
confidence: 99%